What Defines Early Specialization: A Systematic Review of Literature - Mosher, Alexandra; Fraser-Thomas, Jessica; Baker, Joseph (Frontiers in Sports and Active Living, 2020)
Introduction: While practitioners and organizations advise against early specialization, the lack of a consistent and clear definition of early specialization reduces the impact of recommendations and policies in youth sport. An important first step in understanding the consequences of early specialization is establishing what early specialization is. Objectives: This PRISMA-guided systematic review aimed to determine the types, characteristics, and general content of early specialization papers within the literature, and examine how early specialization has been defined and measured in order to advance knowledge toward a clear and consistent definition of early specialization. Data sources: Four different electronic databases were searched (SPORTDiscus, Web of Science, Sports Medicine and Education Index, and Scopus). Both non data-driven and data-driven studies were included to ensure a comprehensive understanding of the literature. Eligibility Criteria: In order to be included in the review, the paper must: (a) Focus on specialization and explicitly use the term “specialization” (b) Focus on sport and athletes (c) Be papers from a peer-reviewed (d) Be in English. And finally, (e) be available in full text. Results: One thousand three hundred and seventy one articles were screened resulting in 129 articles included in the review after applying inclusion/exclusion criteria. Results indicated a clear discrepancy between key components of early specialization and the approaches used to classify early specializers. Conclusion: Future research should work toward developing a valid and reliable approach to classifying early specializers and establishing a consistent definition across studies.